Femoral Artery's Blood Volume Pulse Signal Modelling - Yilmaz, Serdar; Toker, Onur; Arslan, Nurullah (IEEE, 2009)
Cardiovascular diseases are important disease to affecting our world recently. Numerical and experimental simulations are rapidly increasing in this research area. Blood Volume Pulse uses frequently to diagnose and treatment of this kind of disease. Data was obtained from modeling of blood vessel and blood flow in vitro experimental system, supports for instruct to direction diagnose and treatment of disease. Because of that femoral artery blood volume signal modeling was chosen as goal, has important place in cardiovascular area. Suitable for this purpose centrifugal pump, pump driver card, data acquisition card, flow meter and other equipments were established for close loop control mechanism in our university's laboratory. Results of obtained indicate that is available model of the femoral artery blood flow taken data from the real patients. There is the motivation result to improve new approach diagnosed and treatment ways of different blood vein and blood volume pulse signals modeling.
Keywords: Femoral artery; Blood Volume Pulse (BVP); Atherosclerosis; Stenosis; In vitro; HUMAN ABDOMINAL-AORTA; WALL SHEAR-STRESS; IN-VITRO; FLOW; DISEASE; EXERCISE; Engineering